Advances in brain inspired cognitive systems : 8th International Conference, BICS 2016, Beijing, China, November 28-30, 2016, Proceedings /: 8th International Conference, BICS 2016, Beijing, China, November 28-30, 2016, Proceedings. (2016) - Unknown
No abstract available